EFEKTIFITAS PEMBELAJARAN PAI MENGGUNAKAN MODEL PEMBELAJARAN PROBLING PROMPTING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI HARI AKHIR PADA SISWA KELAS VI SDN 06 PANGKATAN - Holidah Yanti Ritonga (CV. ADIBA AISHA AMIRA, 2022)
This research aims (1) to find out whether there is an increase in student learning outcomes in PAI lessons on final day material in class VI SDN 06 Pangkatan using Probing Prompting compared to using conventional learning (2) To find out how the process of increasing student learning outcomes in PAI lessons material final day in class VI at SDN 06 Pangkatan using Probing Prompting. This research is Classroom Action Research. The subjects of this research were Class VI students at SDN 06 Pangkatan, Pangkatan District, Labuhanbatu Regency with a total of 27 students studied, 12 male students and 15 female students. The object of this research is to improve student learning outcomes in PAI learning on final day material by using the Probing Prompting Learning Model. Based on the discussion and research, it can be concluded that learning by applying the Probing Prompting Model can improve PAI Learning Outcomes in Final Day material in class VI SDN 06 Pangkatan, Pangkatan District, Academic Year 2022/2023. In the initial test, there were 15 students (55.56%) who had achieved an individual learning completion level of ≥ 60%, while 12 students (44.44%) had not achieved an individual learning completion level of ≤60% and an average score of 58. 52%. In the first cycle, there were 20 students (74.07%) who had reached the level of individual learning completeness. Meanwhile, 7 students (25.96%) had not reached the level of learning completeness and obtained an average student learning outcome score of 68.89%. In cycle II, there were 24 students (88.89%) who had reached the level of individual learning completeness, while 3 students (11.11%) were still incomplete and the average student learning outcome score was 80.37%. The results of learning management carried out by teachers also increased, namely in cycle I it was 63.64%, increasing to 88.64% in cycle II, while student observations in cycle I were 62.50%, increasing to 83.33% in cycle II.